1984
DOI: 10.1016/0014-5793(84)81021-2
|View full text |Cite
|
Sign up to set email alerts
|

Lectins facilitate calcium‐induced fusion of phospholipid vesicles containing glycosphingolipids

Abstract: Ca2+‐induced fusion of phospholipid vesicles containing globoside (GL‐4) or disialoganglioside (GDla) is several‐fold slower than the fusion of the pure phospholipid vesicles. Lectins specific for these glycosphingolipids, soybean agglutinin and wheat germ agglutinin, respectively, enhance the rate of fusion when added to the vesicle suspension before the introduction of Ca2+. The enhancement depends on the lectin concentration and the time of preincubation with the lectin. We propose that lectins facilitate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1985
1985
1992
1992

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…It is of interest to compare our results with those obtained in recent studies on the effect of glycolipids on the Ca2+-induced fusion of acidic phospholipid-containing vesicles (Sundler & Wijkander, 1983;Düzgünes et al, 1984a). Incorporation of 5-10 mol % of several glycolipids into these vesicles drastically reduces the rate and extent of Ca2+-induced fusion and in certain cases even completely prevents it, as we report for the glycophorin-containing vesicles.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is of interest to compare our results with those obtained in recent studies on the effect of glycolipids on the Ca2+-induced fusion of acidic phospholipid-containing vesicles (Sundler & Wijkander, 1983;Düzgünes et al, 1984a). Incorporation of 5-10 mol % of several glycolipids into these vesicles drastically reduces the rate and extent of Ca2+-induced fusion and in certain cases even completely prevents it, as we report for the glycophorin-containing vesicles.…”
Section: Discussionsupporting
confidence: 78%
“…The influence of several factors, e.g., head-group composition of mixed phospholipid vesicles (Düzgünes et al, 1981a,b;, bilayer curvature (Nir et al, 1982), divalent cation specificity (Wilschut et al, 1981;Bentz et al, 1983), the incorporation of glycolipids in the phospholipid bilayer (Sundler & Wijkander, 1983; Düzgünes et al, 1984a;Hoekstra et al, 1985), lipid-phase separations f These investigations were carried out under the auspices of The Netherlands Foundation for Chemical Research (SON) with financial aid from The Netherlands Organization for the Advancement of Pure Research (ZWO). and membrane hydration (Hoekstra, 1982b), and ionotropic and thermotropic phase transitions (Düzgünes et al, 1984b), on fusion of in particular phosphatidylserine-(PS-)1 containing vesicles has been examined.…”
mentioning
confidence: 99%
“…In the case of PS vesicles, the formation of an anhydrous Ca2+/PS complex of specific stoichiometry, possibly serving as the trigger for membrane fusion, has been suggested (Ekerdt & Papahadjopoulos, 1982), while a similar proposal has been described for PA-containing vesicles (Sundler et al, 1981). Interestingly, the insertion of GL-4 into PS bilayers inhibits both the for- mation of the specific Ca2+/PS complex (Ekerdt & Papahadjopoulos, 1982) and fusion (Düzgünes et al, 1984). The observation that Ca2+ (in the absence of SBA) caused very little fusion of GL-4-containing PE/PA vesicles (Figure 3) suggests that, analogous to the PS system, the presence of the globoside prevented the formation of the specific and fusiontriggering Ca2+/PA complex.…”
Section: Discussionmentioning
confidence: 86%
“…The results in Figure 6 and Table I indicate that polylysine has little effect, if any, on the rate constant of fusion per se, /¡,. In this sense the action of polylysine is similar to that of lectins (Düzgünes et al, 1984) and synexin (Creutz et al, 1979;Hong et al, 1981Hong et al, , 1982, which was shown to enhance the overall rate of vesicle fusion and to reduce the Ca2+ threshold concentration merely by promoting vesicle aggregation, i.e., increasing only Cj| values (Hong et al, 1983). Another confirmation to our conclusion is the fact that removal of polylysine after initiation of fusion does not alter significantly the rate of fusion, while the addition of EDTA terminates the process.…”
Section: Discussionmentioning
confidence: 99%